2023
DOI: 10.1111/os.13742
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Hemivertebrae: The Natural History and Treatment of 50 Patients

Abstract: Objective Multiple hemivertebrae (MHV) is defined as three or more hemivertebrae, and is relatively uncommon among patients with congenital scoliosis. This study aimed to compare the natural history of different kinds of MHV and describe the surgical outcome of MHV. Methods In this retrospective cohort study, a total of 50 patients diagnosed with MHV were enrolled from June 2007 to June 2018. The medical records and radiographs of these patients were reviewed to summarize the characteristics of MHV. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We speculate that the lower scores of self-image and mental health in patients with CS may be attributed to the more severe cosmetic deformities. Furthermore, previous studies have reported that the progression rates for individuals with type II CS, characterized by an unsegmented bar located at the thoracic spine, range from 2° to 6.5° per year ( 26 , 27 ). Therefore, being born with a congenital disease, experiencing rapid deterioration rates, and undergoing long-term repeated hospital visits may be factors that contribute to a decline of HRQoL in patients with CS.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the lower scores of self-image and mental health in patients with CS may be attributed to the more severe cosmetic deformities. Furthermore, previous studies have reported that the progression rates for individuals with type II CS, characterized by an unsegmented bar located at the thoracic spine, range from 2° to 6.5° per year ( 26 , 27 ). Therefore, being born with a congenital disease, experiencing rapid deterioration rates, and undergoing long-term repeated hospital visits may be factors that contribute to a decline of HRQoL in patients with CS.…”
Section: Discussionmentioning
confidence: 99%
“…unilateral unsegmented bar with contralateral hemivertebra) and early preventive surgical treatment. 22 Congenital scoliosis is not reported to be associated with back pain in children. Few case reports published on the coexistence of back pain and congenital scoliosis underline the atypical nature of such a combination (unusual curve pattern, unusual pain type, accidental diagnosis in an apparently healthy individual).…”
Section: Part Ii: Non-idiopathic Scoliosismentioning
confidence: 99%